Правомірна державна допомога суб’єктам господарювання: законодавче відображення - Мельник, Світлана Борисівна; Мельник, С. Б.; Мельник, Светлана Борисовна; Melnyk, Svitlana B.; Melnik, S. B.; Феофанова, Ірина Максимівна; Феофанова, І. М.; Феофанова, Ирина Максимовна; Feofanova, Iryna M.; Feofanova, I. M. (Харків, 2019)
Розглянуто спеціальні норми конкурентного європейського та антимонопольно-конкурентного національного законодавства щодо правомірності надання державної допомоги суб’єктам господарювання. Наводяться відомості про вітчизняні та зарубіжні наукові надбання у сфері диференціації державної допомоги. Розкрито недостатність законодавчого врегулювання та відсутність послідовності і внутрішньої структурованості законодавчих приписів, які стосуються понятійного апарату в цій сфері. Запропоновано новий підхід з позиції правомірності надання державної допомоги суб'єктам господарювання шляхом розподілу її на рівні. Зазначено, що імплементація європейських норм в національне законодавство в сфері державної допомоги призводить до прискореної трансформації інституту державної допомоги. Зроблено висновок, що слід заповнювати прогалини стосовно правомірності державної допомоги суб’єктам господарювання у національному законодавстві з урахуванням європейського досвіду.

With the adoption of a special law in the field of state aid to economic entities, the issues of its legal filling, first of all, the development of secondary legislation, as well as the practical operation of the introduced legislative regulations, was actualized. In view of its international obligations, Ukraine seeks to implement European standards and create the institutional, legal and organizational framework for the functioning of the State aid system. However, effective legal regulation of relations in this area requires categorical certainty; harmonization of the principle of prohibition with its permission, established by the legislator; the clarity of the mechanisms of state aid legalization. Therefore, the question of the legality of state aid to economic undertakings often raises questions. This is due to the lack of legislative regulation and the lack of consistency and internal structure of the legislative provisions, which entails irreversible consequences concerning the conceptual apparatus in this area, in particular, the distortion of the purpose of the aid, its forms, and the reasons for providing it. The purpose of our work is to compare views and approaches to the separation of state aid under different criteria; analysis of national legislation in the field of state aid regarding the legalization of its provision; forming a new approach to the distribution of state aid in terms of its legitimacy. Methods. Research methods: dialectical, formallogical, comparative-legal, system-structural. Results. The novelty of the article is to propose a completely new approach from the point of view of the law-fulness of granting state aid to economic entities by dividing it at the levels based on the current competitive European and national legislation. Conclusions. Based on the conducted research, it is concluded that the problem of the legality of state aid to economic entities has gaps in regulation, which require urgent harmonization of substantive and procedural legislative norms regarding the special Law.
Мельник С. Б. Правомірна державна допомога суб’єктам господарювання: законодавче відображення / С. Б. Мельник, І. М.Феофанова // Форум Права. - № 57(4). - 2019. - С. 59–65.
Keywords: економічна конкуренція; антимонопольно-конкурентне законодавство; обмеження конкуренції; легалізація державної допомоги; economic competition; antitrust and competition law; restriction of competition; legalization of state aid; Research Subject Categories::LAW/JURISPRUDENCE